Synchronous generator system identification via dynamic simulation using PSS/E: Malaysian case - Baswaimi, Saleh; Verayiah, Renuga; Xu, Tan Yi; Panneerchelvan, Nagaraja Rupan; Abidin, Aidil Azwin Zainul; Marsadek, Marayati; Ramasamy, Agileswari K.; Abidin, Izham Zainal; Jaafar, W. Mohd Suhaimi Wan (Institute of Advanced Engineering and Science, 2025)
The synchronous generator (SG) plays a crucial role in power systems by serving as a stable and reliable source of electrical energy. The performance of an SG hinges on its standard parameters, which can be derived through dynamic tests. This study introduces a method for determining the standard parameters of an SG from dynamic tests conducted via power system simulation for engineering (PSS/E). The proposed method entails conducting several key tests on the generator, including a direct-load rejection test, excitation removal test, quadrature-axis load rejection test, arbitrary axis load rejection test, and open-circuit saturation test. The results obtained from these tests are then utilized to calculate the standard parameters of the SG accurately. To validate the effectiveness of the method, simulation data from the SG, as well as the designed initial data, are utilized. Statistical analysis reveals that the maximum relative error is equal to or less than 2.7% of the design values for all standard parameters, emphasizing the robustness and accuracy of the proposed method. The methodology presented in this study can complement field or site measurements, as it enables the verification of system parameters through dynamic simulations.